Investments - Sharpe, William F. (New Jersey : Prentice-Hall Inc., 1985)
The book is intended to be encyclopedic without excessive or insignificant detail, rigorous without the use of needless analytic apparatus, and as integrated as possible.
Includes index
osc 4/8/17
Loans
Keywords: Investments